Chorea-Acanthocytosis in a Chinese Family With a Pseudo-Dominant Inheritance Mode - Yi, Fang; Li, Wenwen; Xie, Nina; Zhou, Yafang; Xu, Hongwei; Sun, Qiying; Zhou, Lin (Frontiers in Neurology, 2018)
Chorea-acanthocytosis (ChAc) is a rare neurodegenerative movement disorder with variable clinical features, including movement disorders, cognitive decline, myopathy, neuropathy, behavioral changes, seizures and acanthocytosis. The majority of ChAc patients display an autosomal recessive mode of inheritance. A pseudodominant way of transmission represents only a rare condition. Few studies have reported the clinical status of the obligate carriers of ChAc. Here, we describe a Chinese ChAc family with a novel mutation in the VPS13A gene, presenting a pseudo-dominant inheritance mode. Our report further expanded the knowledge of phenotypes of ChAc.